Psychological correlates of quality of life in dermatology patients - Potocka, Adrianna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2009)
Objectives: Chronic skin diseases have been recognized as having a detrimentaleffect on patientsć quality of life, also causing considerable mental discomfort. Reduced self-acceptance, low self-esteem, a negative body image, and a low sense of self-worth have been noted in patients with visible skin disorders. Yet in the available literature we could not find any data concerning the relationship between mental health status, self-image, and quality of life. This research, then, analyzes potential relationships betweenself-acceptance, mental health status, and quality of life in dermatology patients. Materials and Methods: In total, 112 patients of the Occupational Diseases Outpatient Clinic and the Occupational and EnvironmentalAllergy Centre of the Nofer Institute of Occupational Medicine (NIOM) were examined. The General Health Questionnaire (GHQ) was used to assess the patientsć mental health; a Polish version of the Dermatology Life Quality Index (DLQI) was employed to assess life quality; and the Self-Acceptance Scale (SAS) served to obtain the patientsć self-image. Resultsshowed that there were statistically significant differences in self-assessment of mental health and quality of life depending on onećs level of self-acceptance. People with high self-acceptance are characterized by better mental health than those with low self-acceptance (t = 4.8; p = 0.00). Patients with a negative selfimage (compared to those with a positive self-image) also deem their quality of life to be poor (t = 3.1; p = 0.00). Results of regression analysis show that mental health status significantly affects the quality of life in dermatology patients; the standardized coefficient was beta = 0.42 (p < 0.0001). Conclusion: Relationships have been found to exist between the patientćs mental health and both their subjective assessment of life quality and self-image. (Abstract truncated at 2000 characters)
Keywords: ankete; dermatitis; Dermatitis alergijski, kontaktni; Dermatitis atopični; Dermatitis, Allergic Contact; Dermatitis, Atopic; dermatologija; Duševne motnje; Kožne bolezni; Kvaliteta življenja; Mental Disorders; Psychology; Quality Of Life; Questionnaires; Samokoncept; Self Concept; Skin Diseases; Urticaria; Urtikarija